PEMBUATAN WEBSITE TEMPAT PARIWISATA RUMAH DOME NEW NGLEPEN - Rudi Banu Kuncoro -PT Usaha Reflektif Indonesia (SPEED - Sentra Penelitian Engineering dan Edukasi, 2017)
Abstract : Dome Housing of New Nglepen, a museum of Earthquake occurred in 2006 which is located in Sengir Prambanan Yogyakarta has been attracting many visitors from all area in Indonenesia even from abroad. This tourism spot has a weakness in their publishing system that causes people are not aware of the existence of a Unique tourism spot. So far, they use a natural publication system which is conducted through casual conversation (word of mouth). It has been encouraging the author to design a profile website to enable global publication throughout the world. The purpose of this research is to buid a profile website for Dome Housing of New Nglepen which will be functioned to introduce the Dome Housing of New Nglepen to all people all over the world that this is one of the most interesting tourism spots in Indonesia. The author expects that it will increase the foreign exchange of Indonesia. The methods used in this research are collecting primary data, collecting secondary data, design, programming, testing, implementation and maintenance.